Violation of the constitutional guarantee to the double instance for the conviction of the acquitted, during the validity of the criminal procedure code in the judicial district of Tacna (2012-2013) - Cutipa Ccaso, Lucio (2015)
Objective: This research aims to: clarify to what extent the constitutional guarantee of plurality of request by the sentence imposed by a higher body of first instance acquitted in the national legal system is violated; and specify the consequence of the violation of human and fundamental rights of the accused referred to in the constitutional and supranational norm during the term of the Criminal Procedure Code in the Judicial District of Tacna (2012-2013). Method: This research is documentary and field, to analyze and describe the infringement of the constitutional right to a second hearing for the conviction of acquittal for the duration of the criminal procedure code in the judicial district of Tacna, and a precise determination the lack of a defense mechanism sentenced on appeal. This research is part of Propositiva- Legal, Thesis applied and legal partner, and aims to challenge a law or valid legal institution, then to assess their failures, to propose changes or legislative reforms in particular. The data collection techniques used to obtain information through the formal registration of chips and electronic bibliographies, internet use tools, and application of word processing software, used as an instrument having the bibliography, Sheet webgraphy and Internet. Technical analysis is also used documentary record, through the doctrinal theoretical analysis of different legal texts and books, and domestic and foreign articles and case law to which the Documentary card was used. Result: The results of the research allowed to identify which is very high the attack on the constitutional principle of double-double instance review and condemned the violation of constitutional principles (right of defense, due process, etc.) and criminal procedural principles (immediacy, concentration, right of defense, etc). As well as the lack of defense mechanisms condemned. Conclusions: high level of infringement of the constitutional right to a second hearing, by the criminal sentence imposed by a collegial body than acquitted at first instance, pursuant to Articles 419.2 and 425.3.b of the Criminal Procedure Code for 2012 and 2013, in the Judicial District of Tacna.